Maker Club in Pre-School - Freitas, L.; Ferrás, A.; Vaz, C.; Fernandes, A. S.; Torres, F.; Queirós, M. I.; Pint, M. B. (Open Schools Journal for Open Science, 2020)
The project allows pre-school children to develop the problematization of what they are learning and, in secondary school, students’ perspectives of cooperative in the development of scientific literacy. In this type of activity, children, with the help of high school students, deepen and consolidate behavioral values for life, thus enabling a positive change in their attitudes, in the way of believing, innovating, planning and persisting to conquer. The activities developed are accessible, both in approach and availability as well as in the cost of materials.